Analysis on Impact of Work Life Balance towards Job Retention on ITES Sector (IT Enabled Service Sector) - Dr. G. Bala Murugan; M.Priya Dharshini (International Journal of Engineering and Management Research, 2023)
This analysis examines the impact of work-life balance on job retention in the Information Technology Enabled Services (ITES) sector. The study utilizes a mixed-methods approach, Combining survey data from ITES employees and qualitative interviews with HR professionals and industry experts. The results indicate that work-life balance has a significant positive impact on job retention in the ITES sector, as employees who perceive a better balance between their work and personal lives are more likely to remain with their current employer. Additionally, the study identifies several factors that contribute to work-life balance, including flexible scheduling, supportive workplace culture, and opportunities for career growth and development. The findings highlight the importance of creating a work environment that prioritizes work-life balance, as it can lead to increased employee satisfaction, productivity, and retention, ultimately benefiting both employees and employers in the ITES sector.